Pengujian Resistensi Staphylococcus aureus Hasil Isolasi Udara Ruang Kelas Sekolah Dasar Di Surakarta terhadap Penisilin G, Metisilin dan Vankomisin - NATHALIA KURNIA ASTRIANI; TITIK SUNARNI; YUDI RINANTO (Fakultas Farmasi Universitas Setia Budi, 2012)
Staphylococcus aureus is the bacteria that cause serious infections. This is supported by the presence of Staphylococcus aureus resistance to antibiotics. Air condition in the Elementary School classroom as a factor enabling the spread of infectious diseases in which elementary school is a community that consist of children aged between 6-12 years on average has not been able to be independent terms of cleanliness. Especially with irrational or excessive use of antibiotics in children appears to be more frequent and increasingly alarming. This research begins by sampling the air of bacteria with medium Vogel Johnson Agar to be opened for 30 minutes in elementary school classrooms. Samples obtained from nine elementary schools in Surakarta. Incubation at 37ºC for 24 hours. Identification test carried Staphylococcus aureus bacteria and then isolated. Staphylococcus aureus obtained is used as the test bacteria to antibiotics penicillin G, methicillin and vancomycin. The result of this study was from 27 point in nine elementary school there are 20 point containing Staphylococcus aureus. Based on sensitivity tests there are 30 % resistant to penicillin G, 5 % for methicillin and not anything for vancomycin. Mean while based on penicillinase test there are 6 point that Staphylococcus aureus produces penicillinase enzyme.